Cross-national agreement on disability weights: the European Disability Weights Project - Burström Kristina; Stouthard Marlies EA; Schwarzinger Michaël; Nord Erik (BMC, 2003)
Abstract Background Disability weights represent the relative severity of disease stages to be incorporated in summary measures of population health. The level of agreement on disability weights in Western European countries was investigated with different valuation methods. Methods Disability weights for fifteen disease stages were elicited empirically in panels of health care professionals or non-health care professionals with an academic background following a strictly standardised procedure. Three valuation methods were used: a visual analogue scale (VAS); the time trade-off technique (TTO); and the person trade-off technique (PTO). Agreement among England, France, the Netherlands, Spain, and Sweden on the three disability weight sets was analysed by means of an intraclass correlation coefficient (ICC) in the framework of generalisability theory. Agreement among the two types of panels was similarly assessed. Results A total of 232 participants were included. Similar rankings of disease stages across countries were found with all valuation methods. The ICC of country agreement on disability weights ranged from 0.56 [95% CI, 0.52-0.62] with PTO to 0.72 [0.70-0.74] with VAS and 0.72 [0.69-0.75] with TTO. The ICC of agreement between health care professionals and non-health care professionals ranged from 0.64 [0.58-0.68] with PTO to 0.73 [0.71-0.75] with VAS and 0.74 [0.72-0.77] with TTO. Conclusions Overall, the study supports a reasonably high level of agreement on disability weights in Western European countries with VAS and TTO methods, which focus on individual preferences, but a lower level of agreement with the PTO method, which focuses more on societal values in resource allocation.